Beta--CCE and FG 7142 increase defensiveness during intraspecies encounters in mice - Sulcová, A; Krsiak, M; Donát, P (Psychopharmacology, 1992)
The effects were ascertained of two partial inverse agonists at benzodiazepine receptors (beta-CCE and FG 7142) on the incidence of timid (defensive-escape), aggressive, sociable and locomotor activities in both timid and aggressive singly-housed male mice, treated with drugs in paired interactions with untreated non-aggressive males. FG 7142 (5 mg/kg) and beta-CCE (8 mg/kg) increased defenses and escapes without producing other behavioral changes in timid mice. FG 7142 (20 mg/kg) and beta-CCE (1-8 mg/kg) moderately increased defenses and alert postures in aggressive mice and this effect was associated with marked reduction of aggressive behavior. FG 7142 (20 and 80 mg/kg) also decreased walking across cage in aggressive mice. It is concluded that beta-CCE and FG 7142 produced behavioral changes which could be interpreted as "anxiogenic".
Keywords: Male; Carbolines; Interpersonal Relations; interpersonální vztahy; mužské pohlaví; Mice, Inbred ICR; úniková reakce; úzkost; Animals; GABA-A Receptor Antagonists; zvířata; pohybová aktivita; Motor Activity; myši; myši inbrední ICR; Escape Reaction; antagonisté receptorů GABA-A; karboliny; Aggression; Mice; agrese; Anxiety